To Live "in Favour of the Human Being" (Saint Irenaeus AH IV 8:2) - Ruiz Aragoneses, Rosa (Concilium, 2025)
Between the pain and suffering we experience lies the meaning we give it. The way in which we position ourselves before God is not indifferent, as much to confront suffering as a way in which we hope for his consolation and we console others. To put suffering first as a privileged path to meeting God, inside our finite and vulnerable humanity, is to miss the ministry of the incarnation and the way in which Christ confronted pain, evil and death. The consoling Spirit which anoints its humanity is the same one which enables us not to accidentality pass by.